A Systematic Literature Review of Managing Universal and Vocational Secondary Education in a Plural System: Equity Challenges, Implementation Readiness, and the Integration of Islamic Education - Deny Haryadi; Revi Permanasari; Hedi Herdiana; Idi Warsah; Eka Apriani; Irwan Fathurrochman (International Journal of Education Research and Development, 2026)
Universal secondary education policies particularly free secondary schooling and the removal of school fees together with efforts to strengthen vocational secondary education, have become central to education reform in many developing countries. However, wider access does not necessarily lead to better quality or greater equity. This systematic literature review brings together research on policy design, governance, implementation capacity, and secondary education outcomes, with special attention to plural systems that include public, private, and faith-based providers, including Islamic education ecosystems. The review groups the evidence into four main areas: (1) policy design and governance; (2) equity, inclusion, and participation; (3) implementation capacity, including financing, teachers, and accountability; and (4) outcomes and transitions, such as learning achievement, employment opportunities, empowerment, and social cohesion. Overall, the findings suggest that these reforms usually raise enrolment, but gender, socio-economic, and regional inequalities often remain. Lower household costs can help substantially, but they do not always improve retention when social norms, indirect costs, and structural barriers continue to limit participation. Rising enrolment can also place pressure on school capacity and learning quality. In vocational education, outcomes tend to improve when curricula reflect labour market needs and are supported by industry partnerships, good teaching, and regular curriculum updates.